The role of optometry in healthcare for visually impaired older adult populations: a Swiss case study - Seifert, Alexander; Nosch, Daniela S. (Frontiers in Health Services, 2024)
BackgroundVisual impairment (VI) is common among older adults aged 70 years and older, and its prevalence increases with advancing age. The optometry profession may play an important role in a patient-centred health system that incorporates medical and psychosocial aspects by working closely with low vision counselling services (LVCS). This paper investigates the current level of cooperation between optometry and LVCS by analysing the referral practice of optometrists to LVCS for the older population with VI, based on the PROVIAGE study.MethodsA national, telephone-based survey of individuals aged ≥70 years and an online survey of professionals in ophthalmology, optometry and LVCS was conducted in 2022 across Switzerland.ResultsThe responses of 154 individuals with VI and 272 professionals (123 ophthalmologists, 126 optometrists and 23 staff of low vision rehabilitation consulting centres) were analysed. Among the respondents with age-related VI, 33.1% stated that they were aware of LVCS. Of these, however, only 11.7% reported that they had visited such centres during the last five years. Sixty-eight percent of respondents attended the ophthalmologist, but only 1.3% went to the optometrist for vision-related problems. Among ophthalmologists, 95.9% indicated that they had referred patients to LVCS, whereas only 58.8% of optometrists had done so.ConclusionsThe results of this study highlighted the relationship between the different clinician referrals, patient needs, and potential barriers preventing referrals towards older adults in Switzerland. A stronger cooperation between professions in the care network will enhance vision care for the ageing population without the need for additional infrastructure.